Urban placemaking and the commercial property investor/developer - Murphy, Laurence (New Zealand geographer, 2024)
Real estate investment companies direct substantial capital flows into built environments and are significant urban place‐makers. Geographers have long been interested in the ‘urbanisation of capital’ but more recently attention has been directed towards the activities of specific property actors. Employing a firm‐level analysis, this paper presents a case study of Kiwi Property, a large‐scale property company with an investment portfolio exceeding $3 billion. The study charts its corporate and financial dynamics and examines examples of its speculative real estate developments. Employing a firm‐level analysis offers insights into complex and contingent investment processes shaping urban placemaking.